Green chemical synthesis of Pd nanoparticles for use as efficient catalyst in Suzuki‐Miyaura cross‐coupling reaction. (21st December 2018) - Phukan, Shreemoyee; Mahanta, Abhijit; Kakati, Dwipen; Rashid, Md. Harunar
Abstract : Herein, we report the synthesis of tiny spherical Pd nanoparticles (NPs) by green chemical method under ambient conditions using flower extract of Lantana camara plant. The size of the Pd NPs is tunable from 4.7 to 6.3 nm by systematically controlling the concentration of either metal ions or plant extract. The synthesized Pd NPs were well characterized by different spectroscopic, microscopic and diffractometric techniques. The Pd NPs offered good size‐dependent catalytic activity in the Suzuki‐Miyaura C‐C coupling reaction under mild reaction conditions in (1: 1) water‐ethanol mixture. The catalyst is stable and exhibited excellent reusability up to three cycles of coupling reaction after which the catalytic activity decreases. Abstract : Size selected Pd NPs were synthesized by green chemical method using flower extract of Lantana camara plant as reducing‐cum‐capping agent. The synthesized Pd NPs were characterized by different spectroscopic and microscopic techniques. The Pd NPs exhibited excellent catalystic activity in the Suzuki‐Miyaura coupling reaction under ambient reaction conditions. These Pd NPs are highly stable and are reusables for C‐C coupling reaction.